Application of Rice Pest Repellent Using ESP32 Microcontroller and Internet of Things Based Sound Wave - Daniel Alfa Puryono; Enggar Panji Pangestu (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to create an automatic pest-repellent system using the Internet of Things. This system uses a microcontroller model ESP32 Devkit and PIR sensor to detect the attack of rice field leafhopper pests. In addition, the application is also equipped with a buzzer and a servomotor that can repel leafhoppers. The circuit can be used to expel leafhoppers because it can emit ultrasonic waves in the range of 40 kHz. The resulting system is IoT-based, so it can be controlled via smartphone. The application can eradicate leafhoppers at a radius of 3 meters and can kill leafhoppers within 2 hours. However, if the distance is 6 meters, this tool can kill leafhoppers and locusts in a 4-hour time interval.